Solvent Quality-Mediated Regioselective Modification of Gold Nanorods with Thiol-Terminated Polymers - Li, Fan (Langmuir : the ACS journal of surfaces and colloids, 2020)
Modification of nanorods (NRs) with functional polymer ligands is of great significance to enhance their surface chemistry and prompt their applications in many fields (e.g., photothermal therapy, bioimaging, and catalysis). However, the regioselective modification of AuNRs still remains a great challenge. Herein, we introduce a facile yet versatile strategy to achieve the regioselective modification of AuNRs through a solvent quality-mediated strategy. By employing a poor solvent of the original ligand cetyltrimethylammonium bromide (CTAB) as the medium in the modification, polymer ligands would selectively graft onto the two ends of AuNRs, while polymer ligands would graft onto the entire surface when employing a good solvent. This strategy demonstrates good reproducibility and is applicable to both hydrophilic and hydrophobic polymer ligand modifications. Moreover, by combing our strategy with the preoccupation route, the two ends and sidewall of AuNRs modified by two different polymers form an "ABA"-type building block, which can further self-assemble into well-ordered superstructures. Our finding provides a new opportunity for multifunctionalization of NRs